Influence of the Activated Carbon Nature and the Aqueous Matrix on the Pesticides Adsorption - Miguel, Natividad; Ormad, María P.; Mosteo, Rosa; Rodríguez, Jorge; Ovelleiro, José L. (IntechOpen, 2011)
None